MOTHER’S BEHAVIOR IN FULFILL NUTRITION STUNTED CHILDREN - Devi Nur Maulidiya; Apriyani Puji Hastuti; Dion Kunto Adi Patria (Indonesian Journal Of Empirical Nursing Sciences, 2024)
Background Stunting is a condition of failure to grow in children so that children are too short for their age. Mother's behavior also influences children's stunting, especially the pattern of providing nutrition to children. The researcher's aim was to determine the behavior of mothers in fulfilling nutrition for stunted children aged 6-24 months in Tanjungarum Village, Sukorejo District, Pasuruan Regency. Method This research method is a quantitative research study with a descriptive research design. This population is all mothers in Tanjungarum Village, Sukorejo District, Pasuruan Regency. The sampling technique used was purposive sampling. The sample for this research was 90 mothers in Tanjungarum Village, Sukorejo District, Pasuruan Regency. This research was conducted in April-June 2022. The measuring instrument used a questionnaire sheet. Results The research results show that almost all mothers' behavior in providing nutrition for stunted children behaves adequately, 63%, a small portion behaves inadequately, 20%, and a small portion behaves well 17). It is hoped that this research can be used as a source of information for mothers, especially for mothers who have children who are stunted so that the children grow and develop well during their growth period.